Water model determines thermosensitive and physicochemical properties of poly(N-isopropylacrylamide) in molecular simulations - Quoika, Patrick K.; Kamenik, Anna S.; Fernández-Quintero, Monica L.; Zacharias, Martin; Liedl, Klaus R. (Frontiers in Materials, 2023)
Poly(N-isopropylacrylamide) (PNIPAM) is a famous representative of thermosensitive polymers. Thermosensitive polymers undergo a phase transition with lower critical solution temperature. Commonly, their phase behavior is linked to a conformational collapse above a certain temperature. This thermosensitive conformational transition is called Coil-Globule transition. In contrast, most other polymers usually show inverse temperature behavior, i.e., an upper critical solution temperature, corresponding to a Globule-Coil transition. Besides their numerous possible applications, thermosensitive polymers are of interest for fundamental research, because of similarities to macromolecular conformational transitions, e.g., protein folding. The counter-intuitive behavior of thermosensitive polymers is commonly associated with solvation effects. Thus, an accurate description of the solvent is crucial for the investigation on thermosensitive polymers in molecular simulations. Here, we investigate the influence of the in silico water model on the thermosensitive Coil-Globule transition in molecular dynamics simulations. To this end, we performed extensive atomistic simulations of the syndiotactic PNIPAM 20-mer at multiple temperatures with eight different water models–four of which are 3-point water models (TIP3P-type) and four are 4-point water models (TIP4P-type). We found that the thermosensitive Coil-Globule transition is strongly influenced by the water model in the simulations. Depending on the water model, the conformational ensemble of the polymer is shifted significantly, which leads to dramatically different results: The estimated transition temperature may span between 255–350 K. Consequently, depending on the description of the solvent, the physicochemical and mechanical properties of these polymers, e.g., the polymer-solvent affinity and persistence length, vary in simulations. These divergent results originate from the varying strength of interactions between polymer and solvent, but also on the bulk state of the solvent. Both these quantities vary between water models. We found that the Lennard-Jones interaction parameter epsilon of the water model correlates with the transition temperature of the polymer. Indeed, the quadrupole moment of the water model shows an even higher correlation with this quantity. Our results suggest a connection between the phase diagram of the solvent and the thermosensitive transition of the polymer.